Distant but Fair: Intra-Team Justice Climate and Performance in Dispersed Teams. Issue 4 (2nd October 2018) - Magni, Massimo; Ahuja, Manju K.; Maruping, Likoebe M.
Abstract: In an attempt to take advantage of distributed knowledge, organizations are increasingly relying on dispersed teams–teams of individuals who primarily utilize information and communication technology (ICT) to collaborate to achieve a shared objective. Team context has often been recognized as an important factor in affecting performance in dispersed team settings. Recent research has called for the consideration of intra-team justice climate in dispersed teams; yet, how it shapes performance for teams at different degrees of dispersion remains unresolved. Drawing on and integrating extant justice climate and Information Systems (IS) literature on team dispersion, we develop a model to better understand the precise nature of the role played by intra-team procedural justice climate in the relationship between team member dispersion and team performance. Responses from 468 team members and supervisors belonging to 101 work teams were used to test the research model. We found that team dispersion and procedural justice climate affect team performance, and that procedural justice alleviates the negative effect of dispersion on performance, indicating that intra-team procedural justice climate can be a lever for mitigating the challenges posed by ICT-based interaction among members. These findings make important contributions to the extant IS literature on dispersed teams by outlining how organizations may mitigate some of the challenges of dispersion and improve team performance by creating an intra-team environment based upon fairness.